Influence of agricultural subsidies and new technologies trends in the Brazilian wheeled tractors commercialization - Melo, Heloisa Mara de; Nagaoka, Alberto Kazushi; Vieira, Francisco Cleber (Revista de Ciências Agroveterinárias, 2012)
The increased use of machinery, chemicals, fertilizers and other inputs considered "modern" in agriculture are associated with the availability of resources for its funding, and in this respect, the policy on agricultural credit has been, traditionally, the most relevant role in the agricultural modernization process in Brazil. The commercialization of agricultural machinery is very sensitive to various factors associated with the development of agriculture as, for example, new planted areas, economic and agricultural policies, new technological trends and processes. The main objective of this study was to analyze the influence of agricultural credit and new technology trends in the wheel tractors commercialization in Brazil. The results showed that the evolution of domestic sales of wheel tractors followed the availability of rural credit, apart from technological developments in relation to the increase in horsepower range of tractors and the adoption of no-tillage system in Brazil.